2015
DOI: 10.1080/13811118.2015.1094367
|View full text |Cite
|
Sign up to set email alerts
|

How Parental Reactions Change in Response to Adolescent Suicide Attempt

Abstract: This study examined parental reactions to adolescents' suicide attempts and the association of reactions with future suicidal self-directed violence. Participants were 81 mothers and 49 fathers of 85 psychiatric inpatient adolescents. Maternal hostility and paternal anger and arguing predicted future suicide attempts. From pre- to post-attempt, mothers reported feeling increased sadness, caring, anxiety, guilt, fear, and being overwhelmed; fathers reported increased sadness, anxiety, and fear. Findings have cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
2
21
0
3
Order By: Relevance
“…In addition, a survey of suicidal behaviour in the ethnographic record found that it often succeeded in influencing mating decisions if the victim survived, such as preventing unwanted marriages, achieving prohibited marriages, and deterring abandonment [46]. After adolescent suicide attempts, parents have been found to express more caring, sympathy and support [102]. Given the enormous financial incentives to suppress MD chemically, it is imperative that mental health researchers convincingly rule out any possible benefits of reactive depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a survey of suicidal behaviour in the ethnographic record found that it often succeeded in influencing mating decisions if the victim survived, such as preventing unwanted marriages, achieving prohibited marriages, and deterring abandonment [46]. After adolescent suicide attempts, parents have been found to express more caring, sympathy and support [102]. Given the enormous financial incentives to suppress MD chemically, it is imperative that mental health researchers convincingly rule out any possible benefits of reactive depression.…”
Section: Discussionmentioning
confidence: 99%
“…Assistindo-os nas várias transições a que estão expostos e ajudando-os nas novas fases facilitando o processo de aprendizagem de competências, pois alguns eventos críticos e alterações circunstanciais podem desencadear mudanças no adolescente, assim como na família, levando-os a transtornos comportamentais, de identidade ou mesmo no seu desempenho (Meleis, Sawyer, Im, Hilfinger Messias, & Shumacher, 2000). Apesar dos estudos de Morgan et al (2013), Buus et al (2014), Greene-Palmer et al (2015) e Ferrey et al (2016) descreverem o acontecimento como crítico para os pais, não se encontra evidência científica no que alude à hospitalização do adolescente e família. Compete à enfermagem assumir um papel facilitador neste processo transaccional, olhando a família e o jovem como parceiros dos cuidados, reconhecendo e desenvolvendo a capacitação familiar para lidar com a situação.…”
Section: Enquadramentounclassified
“…No entanto, existem adolescentes em que as diversas transformações e exigências, necessidades de ajustes e reajustes internos e externos, instabilidade e desequilíbrio, geram dificuldades na gestão do desenvolvimento saudável nos campos afetivo, pessoal, familiar, escolar e de socialização, tornando-os desta forma vulneráveis a comportamentos autolesivos (Trinco & Santos, 2015). Estes comportamentos exercem sobre os pais um mal-estar constante com sentimentos de tristeza, inquietação, ansiedade, culpa e medo do futuro (Greene-Palmer et al, 2015). De acordo com o Plano Nacional de Prevenção do Suicídio 2013-2017 (Direção--Geral da Saúde, 2013) são considerados comportamentos autolesivos, os comportamentos que envolvem atos autolesivos com ou sem intencionalidade suicida, tais como: ingestão de uma substância ou objeto não ingerível, ingestão de fármacos em doses superiores às dosagens terapêuticas, ingestão de uma droga ilícita ou substância psicoativa com intencionalidade deliberada de autoagressão, saltar de um lugar relativamente elevado e automutilação.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In considering what predicts a suicide reattempt in 13-18 year old adolescents, researchers Greene-Palmer, Wagner, Neely, Cox, Kochanski, Perera, & Ghahramanlou-Holloway (2015) looked to parent reactions after their child made their first attempt. Eighty-one mothers and 49 fathers were surveyed in the mid-Atlantic United States, and responded to questions regarding their reactions to their teen's suicidal behavior.…”
Section: Risk Factors Of Adolescent Suicidementioning
confidence: 99%